2024
DOI: 10.1101/2024.01.25.577285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reference-free Structural Variant Detection in Microbiomes via Long-read Coassembly Graphs

Kristen D. Curry,
Feiqiao Brian Yu,
Summer E. Vance
et al.

Abstract: Bacterial genome dynamics are vital for understanding the mechanisms underlying microbial adaptation, growth, and their broader impact on host phenotype. Structural variants (SVs), genomic alterations of 10 base pairs or more, play a pivotal role in driving evolutionary processes and maintaining genomic heterogeneity within bacterial populations. While SV detection in isolate genomes is relatively straightforward, metagenomes present broader challenges due to absence of clear reference genomes and presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In particular, co-assembly-based approaches-in which reads from multiple samples are combined to create a single joint assembly-have been previously employed for de novo copy number variation detection between two genomes 16 , as well as for calling SVs within microbiomes 17 . Another study demonstrated improved performance for both read alignment and SV calling by using a personalized reference genome assembled from tumor and matched normal samples 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, co-assembly-based approaches-in which reads from multiple samples are combined to create a single joint assembly-have been previously employed for de novo copy number variation detection between two genomes 16 , as well as for calling SVs within microbiomes 17 . Another study demonstrated improved performance for both read alignment and SV calling by using a personalized reference genome assembled from tumor and matched normal samples 18 .…”
Section: Introductionmentioning
confidence: 99%